Beyond the Storms: Strengthening Preparedness, Response, & Resilience in the 21st Century - Dane S. Egli (Journal of Strategic Security, 2013)
Looking Beyond the Storms of major events and reactionary tendencies to prevent future disasters—and continuing to fix things—the author introduces a fresh assessment in the wake of Superstorm Sandy, the vexing challenge of domestic shootings, and a persistent nationwide drought. This paper offers a refreshing perspective on the need for transformational and innovative thinking on preparedness, response, and resilience, as well as disaster management. Against the backdrop of 9-11 terrorist attacks and natural disasters such as hurricanes Katrina, Irene, and Sandy, this paper, highlights that we—as homeland security planners and policymakers—must look beyond the immediate demands of grant proposals and a narrow focus on “prevention” and “protection” to a systemic analysis of “mitigation, response, and recovery”—based upon required functions and capabilities. It asserts the need for change from spending scarce dollars to prevent that which is inevitable and nervously trying to protect physical locations—in an environment of growing complexity and uncertainty—to a posture that integrates resilience as an active virtue in all elements of the homeland security enterprise. There is a sense of urgency that challenges leaders to understand the strategic imperatives and unique opportunities in building all-hazards community resilience.